Effects of lighting system on employee's performances / Nur Asilah Abdul Ghani - Abdul Ghani, Nur Asilah (Faculty of Architecture, Planning and Surveying, 2015)
The lighting system at the offices can play a vital roles to the employees’ performances. It can give good or bad effects to employee’s mood, health, safety and performances. Although the office provides lighting system, but sometimes the employees may faces several problem that related with the lighting such as headache, eye strain, fatigue and sleepiness. The lighting provided may be too dim or too bright for the employees to perform their task. This academic project is aimed to study about the proper lighting system at building offices that gives effect to employee’s performances. It can be determined by answering all the objectives of this study. The objectives are to know the types of lighting that usually used in office building, to investigates the level of expectation and level of satisfaction of employees towards the lighting system at their offices and lastly, to determine whether the lighting system at the building office achieve the employee’s expectation or not. In order to meet all the objectives, the data must be collected. There are two methods conducted for this study which is literature review and questionnaires. The respondents of the questionnaire are among the employees at the office and it conducted at two case studies which is Menara A Pandan Kapital and Menara MPAJ. The data collected then would be analyzed to get the answer for the objectives of this academic project.